Bioremediation and decontamination potential of flagellate Poteriospumella sp. Issue 3 (3rd July 2019) - Syed, Tahira; Batool, Uzma; Aslam, Muhammad; Noreen, Zobia; Farheen, Ifra; Gondal, Asif; Usman Shah, Syed Muhammad; Pucciarelli, Sandra; Bokhari, Habib
Abstract: Water pollution due to heavy metals and water borne pathogen is one of the significant public health issues for developing countries in particular where safe drinking water supply is depleting rapidly. Flagellates are aquatic microscopic organisms that have developed excellent survival strategies, which help them withstand environmental stresses and therefore can act as natural biocontrol in complex ecological systems. This study investigates the wastewater treatment and bioremediation potential of flagellate Poteriospumella sp. Poteriospumella sp. was isolated from northern areas of Pakistan and identified by using 18SrRNA analysis. Wastewater samples were collected from nullah (S1) and two industrial areas of Islamabad and Rawalpindi (S2 and S3) and physiochemical properties (Biological oxygen demand, dissolved oxygen, total nitrogen, ammonia, phosphate and sulfate) were analyzed initially and after treatment with Poteriospumella sp. alone and in combination with consortia of four already characterized bacterial strains i.e., Pseudomonas sp., Salmonella sp., Citrobacter sp., and Enterobacter sp. for 15 days. Furthermore, the bacterivores potential of flagellates was investigated against commonly found endemic waterborne pathogen i.e. Vibrio cholera as well as their ability to sequester or remove heavy metal, mercury (Hg), was also evaluated. The results clearly showed the excellent potential of flagellates in improving wastewater physiochemical properties of all the three wastewater samples i.e. the removal range of BOD (0–10.5%), DO (7.8–38.2%), TN (11.6–53.6%), ammonia (2.7–33.5%), phosphate (0–40%) and sulfate (5.1–12.5%) was recorded. In nutshell, Poteriospumella sp. showed excellent bioremediation potential against Hg (removal of 92–93% of mercuric ions within 2 weeks). In addition, it has significantly reduced the CFU's of unique subtypes of Vibrio cholerae types circulating in Pakistan and hence can be employed as natural predator to control cholera transmission through water.